Sun protection for preventing basal cell and squamous cell skin cancers (2016)
Background'Keratinocyte cancer' is now the preferred term for the most commonly identified skin cancers basal cell carcinoma (BCC) and cutaneoussquamous cell carcinoma (cSCC), which were previously commonly categorised as non-melanoma skin cancers (NMSC). Keratinocytecancer (KC) represents about 95% of malignant skin tumours. Lifestyle changes have led to increased exposure to the sun, which has,in turn, led to a significant increase of new cases of KC, with a worldwide annual incidence of between 3% and 8%. The successful useof preventive measures could mean a significant reduction in the resources used by health systems, compared with the high cost of thetreatment of these conditions. At present, there is no information about the quality of the evidence for the use of these sun protectionstrategies with an assessment of their benefits and risks.ObjectivesTo assess the effects of sun protection strategies (i.e. sunscreen and barrier methods) for preventing keratinocyte cancer (that is, basal cellcarcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC) of the skin) in the general population.Search methodsWe searched the following databases up to May 2016: the Cochrane Skin Group Specialised Register, CENTRAL, MEDLINE, Embase, andLILACS. We also searched five trial registries and the bibliographies of included studies for further references to relevant trials.Selection criteriaWe included randomised controlled clinical trials (RCTs) of preventive strategies for keratinocyte cancer, such as physical barriers andsunscreens, in the general population (children and adults), which may provide information about benefits and adverse events related tothe use of solar protection measures. We did not include trials focused on educational strategies to prevent KC or preventive strategiesin high-risk groups. Our prespecified primary outcomes were BCC or cSCC confirmed clinically or by histopathology at any follow-up andadverse events.